Influence of cationic lipid concentration on properties of lipid–polymer hybrid nanospheres for gene delivery - Rajendran JC Bose; Yoshie Arai; Jong Chan Ahn; Hansoo Park; Soo‐Hong Lee (2015)
Abstract: Nanoparticles have been widely used for nonviral gene delivery. Recently, cationic hybrid nanoparticles consisting of two different materials were suggested as a promising delivery vehicle. In this study, nanospheres with a poly(D,l-lactic- co -glycolic acid) (PLGA) core and cationic lipid shell were prepared, and the effect of cationic lipid concentrations on the properties of lipid polymer hybrid nanocarriers investigated. Lipid–polymer hybrid nanospheres (LPHNSs) were fabricated by the emulsion-solvent evaporation method using different concentrations of cationic lipids and characterized for size, surface charge, stability, plasmid DNA-binding capacity, cytotoxicity, and transfection efficiency. All LPHNSs had narrow size distribution with positive surface charges (ζ-potential 52–60 mV), and showed excellent plasmid DNA-binding capacity. In vitro cytotoxicity measurements with HEK293T, HeLa, HaCaT, and HepG2 cells also showed that LPHNSs exhibited less cytotoxicity than conventional transfection agents, such as Lipofectamine and polyethyleneimine–PLGA. As cationic lipid concentrations increased, the particle size of LPHNSs decreased while their ζ-potential increased. In addition, the in vitro transfection efficiency of LPHNSs increased as lipid concentration increased. Keywords: core–shell hybrid nanospheres, lipid concentration, surface modification, low cytotoxicity, transfection efficiency